Trends in incidence, survival and initial treatments of gynecological sarcoma: a retrospective analysis of the United States subpopulation - Xi He; Qiang Dong; Changfang Weng; Jianfen Gu; Qiao Yang; Guangrong Yang (BMC, 2023)
Abstract Background To estimate the incidence, prevalence and incidence-based mortality in patients with gynecologic sarcoma (GS), and described the trends of survival and initial treatments in the US by using the Surveillance, Epidemiology, and End Results (SEER) database. Methods GS cases aged 20 years or older between 1975 and 2015 were identified from SEER 9 registries. Incidence, prevalence, and incidence-based mortality were estimated, all rates were age adjusted to the 2000 US standard population and presented as per 100,000 persons. Annual percentage change (APC) and average APC (AAPC) were calculated to describe the trends. In addition, stage distribution, cancer-specific survival (CSS) and initial treatment pattern over time were also reported. Results The overall age-adjusted incidence of GS increased from 2.38 to 3.41 per 100,000 persons from 1975 to 2015, with an AAPC of 1.0 (P < 0.05), and the AAPC increased to 1.3 (P < 0.05) in the last decade. The incidence of population aged ≥ 55 years was three or more times than that of population aged 20-54 year from 1975 to 2015. Corpus and uterus GS was the main subtype, and it increased significantly during last three decades (an APC of 1.5). In addition, the prevalence of corpus and uterus GS increased mostly among all GSs. The incidence of GS with regional and distant stages increased pronouncedly, but not for local stage. GS cases showed increasing 3-year and 5-year CSS rates except for other sites GS. Approximately 87.7% GS cases received surgery during the first-course treatment, but the proportion decreased over years. In contrast, the proportion of receiving multiple treatment modalities increased. Conclusions The incidence of GS increased significantly with improved survival, which might due to the strategy of combination of multiple treatment. However, no obvious improvement on the early detection of GS was found, which should be facilitated to further improve the prognosis of GS.